1996
DOI: 10.1093/nar/24.10.1954
|View full text |Cite
|
Sign up to set email alerts
|

The histone 3'-terminal stem-loop is necessary for translation in Chinese hamster ovary cells

Abstract: The metazoan cell cycle-regulated histone mRNAs are the only known cellular mRNAs that do not terminate in a poly(A) tall. Instead, mammalian histone mRNAs terminate in a highly conserved stem-loop structure which is required for 3'-end processing and regulates mRNA stability. The poly(A) tail not only regulates translational efficiency and mRNA stability but is required for the function of the cap in translation (m(7)GpppN). We show that the histone terminal stem-loop is functionally similar to a poly(A) tail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
74
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(80 citation statements)
references
References 48 publications
6
74
0
Order By: Relevance
“…The 39 end of histone mRNA and its bound SLBP play a critical role in multiple aspects of histone mRNA metabolism, including pre-mRNA processing (Dominski et al+, 1995;Wang et al+, 1996c;Martin et al+, 1997), export (Eckner et al+, 1991;Williams et al+, 1994), translation (Sun et al+, 1992;Gallie et al+, 1996), and mRNA stability (Pandey & Marzluff, 1987;Williams et al+, 1994)+ The frog oocyte is a convenient experimental system to study the many aspects of RNA metabolism because one can express or inject both specific RNAs and proteins and follow their subsequent metabolism+…”
Section: Resultsmentioning
confidence: 99%
“…The 39 end of histone mRNA and its bound SLBP play a critical role in multiple aspects of histone mRNA metabolism, including pre-mRNA processing (Dominski et al+, 1995;Wang et al+, 1996c;Martin et al+, 1997), export (Eckner et al+, 1991;Williams et al+, 1994), translation (Sun et al+, 1992;Gallie et al+, 1996), and mRNA stability (Pandey & Marzluff, 1987;Williams et al+, 1994)+ The frog oocyte is a convenient experimental system to study the many aspects of RNA metabolism because one can express or inject both specific RNAs and proteins and follow their subsequent metabolism+…”
Section: Resultsmentioning
confidence: 99%
“…SLBP is required for the translation of stem-loop histone mRNAs (Sun et al, 1992;Gallie et al, 1996), and we have recently shown that SLBP stimulates translation of histone mRNA in vivo and in vitro (Sanchez and Marzluff, 2002). The SLBP that accumulates during maturation may play a role in activating translation of histone mRNA during oocyte maturation and after fertilization, thus providing the histone proteins necessary both for repackaging the sperm chromatin and for synthesis of histone proteins for the first S-phase.…”
Section: Discussionmentioning
confidence: 99%
“…An enhancing effect by the 3Ј-UTR has been observed for nonpolyadenylated histone mRNAs, the 3Ј stem-loop of which mimics a poly(A) tail (31), and for amyloid precursor protein and lipoprotein lipase mRNAs, which interestingly contain two alternative poly(A) sites (27,28). A few 3Ј translational enhancers have also been characterized in uncapped and/or unpolyadenylated viruses.…”
Section: Figmentioning
confidence: 99%